Learn more about

Refine search

Results (displaying matches 1-50 of 14681) Next

Label Class Equation Sato-Tate \(\overline{\Q}\)-simple \(\GL_2\) Rank*
295.a.295.2 295.a \(y^2 + (x^2 + x + 1)y = x^5 - 40x^3 + 22x^2 + 389x - 608\) $\mathrm{USp}(4)$ 0
336.a.172032.1 336.a \(y^2 + (x^3 + x)y = -x^6 + 15x^4 - 75x^2 - 56\) $G_{3,3}$ 0
523.a.523.2 523.a \(y^2 + xy = x^5 - 31x^4 - 110x^3 + 21x^2 - x\) $\mathrm{USp}(4)$ 0
644.a.659456.1 644.a \(y^2 + (x^2 + x)y = -3x^6 - 13x^5 + 4x^4 + 51x^3 + 4x^2 - 13x - 3\) $G_{3,3}$ 0
708.a.181248.1 708.a \(y^2 + (x^3 + 1)y = -x^6 - 4x^5 + 9x^4 + 48x^3 - 41x^2 - 98x - 36\) $\mathrm{USp}(4)$ 0
784.b.25088.1 784.b \(y^2 + (x^2 + 1)y = -x^6 - 3x^5 + 7x^4 + 2x^3 - 49x^2 + 41x - 9\) $G_{3,3}$ 0
810.a.196830.1 810.a \(y^2 + (x + 1)y = x^5 + 15x^4 + 20x^3 - 297x^2 + 94x - 8\) $N(G_{1,3})$ 0
880.a.225280.1 880.a \(y^2 = x^5 + 13x^4 + 55x^3 + 76x^2 - 44\) $G_{3,3}$ 0
1062.a.6372.1 1062.a \(y^2 + (x^3 + 1)y = x^5 - x^4 + x^2 - x\) $\mathrm{USp}(4)$ 1
1077.a.1077.2 1077.a \(y^2 + (x^3 + 1)y = x^4 + x^3 + 2x^2 + x\) $\mathrm{USp}(4)$ 1
1077.a.1077.1 1077.a \(y^2 + (x^3 + 1)y = 5x^5 + 34x^4 + 80x^3 - x^2 - 90x + 32\) $\mathrm{USp}(4)$ 1
1104.b.141312.1 1104.b \(y^2 + (x^3 + x)y = -x^6 - 3x^4 + 29x^2 - 46\) $G_{3,3}$ 0
1145.a.1145.1 1145.a \(y^2 + (x^3 + 1)y = -3x^4 + 3x^3 - x\) $\mathrm{USp}(4)$ 1
1145.a.143125.1 1145.a \(y^2 + (x^3 + x^2 + x)y = 2x^4 + 4x^3 + 9x^2 + 10x + 9\) $\mathrm{USp}(4)$ 1
1216.a.19456.1 1216.a \(y^2 + x^2y = 4x^5 + 3x^4 - 11x^3 - 6x^2 + 6x - 1\) $\mathrm{USp}(4)$ 0
1270.a.325120.1 1270.a \(y^2 + (x^2 + x)y = x^5 + 17x^4 + 76x^3 + 14x^2 - 32x + 3\) $\mathrm{USp}(4)$ 0
1309.a.9163.2 1309.a \(y^2 + x^2y = -x^6 + 20x^5 - 128x^4 + 248x^3 + 32x^2 + x\) $\mathrm{USp}(4)$ 0
1312.a.2624.1 1312.a \(y^2 + (x + 1)y = x^6 + 2x^5 + 3x^4 + 2x^3 + x^2\) $\mathrm{USp}(4)$ 1
1328.a.1328.1 1328.a \(y^2 + x^2y = x^5 - 3x^4 - 9x^3 - 5x^2 - 4x - 5\) $\mathrm{USp}(4)$ 0
1338.a.2676.1 1338.a \(y^2 + (x^3 + x^2 + x)y = x^4 + x^3 + 2x^2 + x + 1\) $\mathrm{USp}(4)$ 1
1415.a.1415.1 1415.a \(y^2 + (x^2 + x + 1)y = x^5 - 3x^4 + x^3 - x\) $\mathrm{USp}(4)$ 1
1445.a.122825.1 1445.a \(y^2 + (x^3 + x^2 + x)y = 3x^4 + 4x^3 + 18x^2 + 10x + 29\) $\mathrm{USp}(4)$ 1
1490.a.1490.1 1490.a \(y^2 + (x^3 + 1)y = x^5 - 4x^3 - 2x^2 + 2x\) $\mathrm{USp}(4)$ 1
1595.a.231275.1 1595.a \(y^2 + (x^3 + x)y = x^4 - x^3 + 2x^2 - 4x + 1\) $\mathrm{USp}(4)$ 1
1655.a.1655.1 1655.a \(y^2 + (x^3 + x^2 + x)y = x^3 - x\) $\mathrm{USp}(4)$ 1
1655.a.206875.1 1655.a \(y^2 + (x^3 + 1)y = x^5 - x^4 - 7x^3 + 2x^2 + 14x - 10\) $\mathrm{USp}(4)$ 1
1664.a.3328.1 1664.a \(y^2 + xy = x^6 - 2x^5 - x^4 + 3x^3 - x\) $\mathrm{USp}(4)$ 1
1689.a.1689.1 1689.a \(y^2 + (x^2 + x + 1)y = x^5 + 2x^4 + 2x^3 + x^2\) $\mathrm{USp}(4)$ 1
1689.a.45603.1 1689.a \(y^2 + (x^2 + x + 1)y = x^5 - 6x^4 + 21x^3 + 15x^2 + 3x\) $\mathrm{USp}(4)$ 1
1696.a.217088.1 1696.a \(y^2 + (x^2 + 1)y = x^5 - 24x^4 - 28x^3 - 22x^2 - 7x - 1\) $\mathrm{USp}(4)$ 0
1702.a.39146.1 1702.a \(y^2 + (x + 1)y = x^5 - 13x^3 + 14x^2 + 22x - 30\) $\mathrm{USp}(4)$ 1
1738.a.137302.1 1738.a \(y^2 + xy = x^5 - 5x^3 - 66x^2 - 101x - 41\) $\mathrm{USp}(4)$ 0
1888.a.483328.2 1888.a \(y^2 = x^5 + 8x^4 + 8x^3 - 31x^2 + 20x - 4\) $\mathrm{USp}(4)$ 0
1899.a.5697.1 1899.a \(y^2 + (x^3 + 1)y = -x^5 + x^4 - 3x + 2\) $\mathrm{USp}(4)$ 1
1929.a.1929.1 1929.a \(y^2 + (x^2 + x + 1)y = x^5 - x^4 + x^3 - x^2\) $\mathrm{USp}(4)$ 1
1935.a.52245.2 1935.a \(y^2 + xy = x^5 - 2x^4 - 82x^3 - 20x^2 + 927x - 1134\) $\mathrm{USp}(4)$ 0
1985.a.1985.1 1985.a \(y^2 + (x^3 + 1)y = x^5 + x^4 - x\) $\mathrm{USp}(4)$ 1
2007.a.6021.1 2007.a \(y^2 + (x^2 + x + 1)y = x^6 + x^4\) $\mathrm{USp}(4)$ 1
2020.a.646400.1 2020.a \(y^2 + x^3y = 2x^4 - x^3 + 5x^2 - 4x + 4\) $\mathrm{USp}(4)$ 1
2054.a.4108.1 2054.a \(y^2 + (x + 1)y = x^5 + 2x^4 - x^3 - 2x^2\) $\mathrm{USp}(4)$ 1
2056.a.4112.1 2056.a \(y^2 + (x^3 + x)y = x^3 + x^2 + x\) $\mathrm{USp}(4)$ 1
2061.a.6183.1 2061.a \(y^2 + (x^3 + 1)y = -x^4 - x\) $\mathrm{USp}(4)$ 1
2075.a.10375.1 2075.a \(y^2 + (x^3 + 1)y = -2x^4 + x^2 - x\) $\mathrm{USp}(4)$ 1
2085.a.6255.1 2085.a \(y^2 + (x^2 + x + 1)y = -x^6 + 2x^4 - x^2\) $\mathrm{USp}(4)$ 1
2094.a.12564.1 2094.a \(y^2 + (x + 1)y = x^5 - 2x^4 - x^3 + 2x^2\) $\mathrm{USp}(4)$ 1
2127.a.6381.1 2127.a \(y^2 + (x^2 + 1)y = 3x^5 - 6x^4 + 4x^2 + 2x\) $\mathrm{USp}(4)$ 1
2165.a.2165.1 2165.a \(y^2 + (x^3 + 1)y = x^5 - 3x^3 + x^2 + 3x - 2\) $\mathrm{USp}(4)$ 1
2165.a.270625.1 2165.a \(y^2 + (x^2 + x + 1)y = x^5 + 6x^4 - 4x^3 + x\) $\mathrm{USp}(4)$ 1
2173.a.89093.1 2173.a \(y^2 + (x^3 + x^2 + x)y = x^4 + 3x^3 + 3x^2 + 6x + 1\) $\mathrm{USp}(4)$ 1
2178.b.287496.1 2178.b \(y^2 + (x^2 + x)y = -x^6 - 2x^5 + 3x^4 - 8x^2 + 9x - 3\) $G_{3,3}$ 0
Next

Download all search results for